Chronic aspirin and statin therapy in patients with impaired renal function and acute coronary syndromes: results from the IN-ACS Outcome Registry. (29th August 2020) - Sciahbasi, Alessandro; Rizzello, Vittoria; Gonzini, Lucio; Giampaoli, Simona; Greco, Cesare; Di Pasquale, Giuseppe; Mureddu, Gian Francesco; Di Chiara, Antonio; Lioy, Ernesto; Boccanelli, Alessandro
Abstract: Background: The cardioprotective role that statin and aspirin has appears to be reduced in patients with chronic kidney disease (CKD). This analysis aims to evaluate the impact of statin and aspirin on the outcome of patients with CKD and acute coronary syndrome (ACS). Methods: All patients who were enrolled in the IN-ACS Outcome registry, diagnosed with CKD, were included in our analysis. We divided patients into four groups, according to previous chronic therapy: neither aspirin nor statin therapy (Group 1), aspirin only therapy (Group 2), statin only therapy (Group 3) and aspirin plus statin therapy (Group 4). Results: Of the 5483 patients enrolled that had data on glomerular filtration rate available, 1484 had CKD: These segregated into 589 patients in Group 1, 477 in Group 2, 89 in Group 3 and 329 in Group 4. Despite having a higher baseline risk profile, groups 3 and 4, as compared to the other two groups, exhibited a significantly lower in-hospital mortality (1% in Group 3, 2% in Group 4; but 8% in Group 1 and 7% in Group 2, p = 0.0007); while at 30 days it remained so, as it was 1% in Group 3, 4% in Group 4 (and 10% in Group 1 and 10% in Group 2 p = 0.0002); and at 1 year it was 11% in Group 3 and 13% in Group 4 (compared to 20% in Group 1 and 23% in Group 2, p = 0.0012). Conclusions: In a large cohort of patients with CKD and ACS, chronic treatment with statin or the combination of aspirin and statin is associated with short-term and long-term better outcomes for in-hospital mortality, as compared to those receiving no therapy or aspirin therapy alone.